2016
DOI: 10.3390/buildings6010005
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the Uncertainty Related to Building Occupants with Regards to Visual Comfort: A Literature Survey on Drivers and Models

Abstract: Abstract:The interactions between building occupants and control systems have a high influence on energy consumption and on indoor environmental quality. In the perspective of a future of "nearly-zero" energy buildings, it is crucial to analyse the energy-related interactions deeply to predict realistic energy use during the design stage. Since the reaction to thermal, acoustic, or visual stimuli is not the same for every human being, monitoring the behaviour inside buildings is an essential step to assert dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
2
7
0
1
Order By: Relevance
“…In contrast, the closing behaviour during departure and the opening behaviour during arrival were influenced by the absence duration. Fabi's review of the physical predictors that influence light switching behaviour identified the key drivers absence duration and daylight [273]. Season, light sensor control, and time spent with the light off were not significant.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the closing behaviour during departure and the opening behaviour during arrival were influenced by the absence duration. Fabi's review of the physical predictors that influence light switching behaviour identified the key drivers absence duration and daylight [273]. Season, light sensor control, and time spent with the light off were not significant.…”
Section: Resultsmentioning
confidence: 99%
“…The survey was prepared following standards ISO 10551 [57]. Several studies adopt the subjecting approach by submitting surveys [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Sometimes, particular conditions or particular users, such as children in a 4-5 years age range [15,63], require the survey to be integrated or adapted to facilitate the understanding and the filling procedure.…”
Section: Subjective Approach: Thermal Comfort Surveymentioning
confidence: 99%
“…[18], as well as visual comfort inside buildings -Yao, J. [19], Fabi, V. [20], and in industrial operations. Gou, Z. et al studied visual comfort and simulated lighting effects in relation to the productivity and well-being of the population [21,22].…”
Section: Sustainability In Industrial Building Designmentioning
confidence: 99%